Pemberdayaan metakognitif mahasiswa melalui model pembelajaran jinemam - Dwi Candra Setiawan; Deni Setiawan (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2020)
The implementation model of learning that empowers students metacognitive has not run optimally. The jinemam learning model is a learning model developed to empower students' metacognitive abilities. This study aims to determine the effect of jinemam on students' metacognitive. The research used was a quasi-experimental study, where the sample is 2016 batch students of Biology Education. Class A as an experimental class and class B as a control class. The instruments used were syllabus, SLP (Semester Lecture Plan), essay tests and metacognitive assessment rubrics. Research data in the form of quantitative data obtained from the pretest and posttest scores and metacognitive assessment rubric scores. Analysis of research data was performed withthe ANACOVA test through SPSS 22 software. The results showed that there was an influence of the jinemam learning model on the metacognitive abilities of students (p < 0,05). Thus, the conclusion of this research is the learning model of jinemam influences the students' metacognitive abilities